Bibliometric Analysis of Road Performance and Level of Service (LoS) Using VOSviewer - Indra Permana; Adhitya Akta Permana; Anisa Awaliyah; Asep Dian Herdiyana; Joewono Prasetijo (LEADER: Civil Engineering and Architecture Journal, 2025)
This study aims to identify research trends, dominant themes, and keyword linkages in the scientific literature on road performance and level of service (LoS) using a bibliometric approach. Bibliographic data were collected from 1,000 publications using Publish or Perish and analyzed using VOSviewer software. The visualization results showed that the keywords "road performance", "traffic volume", "delay" and "capacity" were the main focus of the studies, reflecting the dominance of technical approaches based on operational indicators. The analysis also revealed a division of themes into several clusters, such as policy evaluation, technical aspects, and methodological approaches. The distribution of publications shows a significant upward trend since 2011, with a peak in 2022-2023. Authors from Indonesia are the largest contributors, although international publications are still dominated by developed countries. These findings indicate the need for a multidisciplinary approach to road performance assessment, including the integration of technical and social data, and the use of spatial technologies such as GIS to support more inclusive and sustainable transportation planning.